Challenges of teaching English online in Asian countries (Eurasian Journal of Learning and Academic Teaching, 2023)
Teaching English online has become an increasingly popular option for both teachers and students around the world. The convenience and flexibility of online teaching allow teachers to work from anywhere, and students to learn at their own pace and on their own schedule. In addition to the benefits of online teaching, there are also unique challenges that arise, particularly when teaching English in Asian countries.